PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 4 RAMBAH - -, Een; -, Hardianto; Afri, Lusi Eka (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This study examines the effect of cooperative learning model Group Investigation (GI) on the results of students mathematicslearning. The population in this study class VIII SMP Negeri 4 Rambah. The sampling technique is done by sampling of saturated.Samples VIII1class as the experimental class and the class as a class VIII2 control. With the test of normality and homogeneity testsshowed the two samples are normally distributed and homogeneous. Analysis of the data using the t test with Î± = 0.05 indicatestcoun=1,946 and ttable= 1.701, tcount> ttable so that H0 is rejected. So it is concluded that there are significant Group Investigation (GI)cooperative learning model for students mathematics learning outcomes